Fast anion-conduction in oxynitrides: oxygen and nitrogen transport in (Y, Zr)-(O, N) - Kilo, Martin; Taylor, Marcela Andrea; Borchardt, Günter; Kaiser-Bischoff, Ines; Boysen, Hans; Rödel, Christoph; Lerch, Martin (Diffusion Fundamentals, 2008)
Cation doped zirconium oxynitrides (for example zirconium oxide doped with yttrium oxide and nitrogen, ''YZrON''), having a fluorite-based structure, are suggested to have fairly high nitrogen diffusivity, besides their high oxygen mobility. In the present work, the tracer-diffusion of nitrogen and oxygen was measured in single crystalline ''YZrON''. Results are compared to the migration pathways and migration enthalpies of nitrogen and oxygen ions as determined by elastic neutron diffraction studies. Excellent agreement of the measured activation enthalpies of nitrogen diffusion (about 2 eV) and oxygen diffusion (about 1 eV) determined by the two methods is found.